QUARTER LIFE CRISIS DALAM PENCIPTAAN SENI LUKIS - Ummi Shabrina Damas (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
One of the events that occurs when someone transitions from adolescence to adulthood is the quarter life crisis. Quarter life crisis is a condition where a person feels worried because of uncertainty about the future. This worry is related to social relationships, careers and social life experienced by individuals aged 20-30 years. The author will invite readers to examine several factors that cause the Quarter Life Crisis and how to overcome it based on the author's experience expressed through painting. This work of art was created by the artist with the aim of reflecting on the conditions around him, encouraging people to be more critical of their environment, and learn together to create a better life in the future. The result of all these paintings is a strong visual combination of three main concepts, namely Quarter life crisis, Sandwich generation, and Hustle culture. Through these paintings, the author succeeds in depicting the complexity of the challenges faced by the younger generation in their transition to adulthood, with the pressure to find meaning in life, fulfill family responsibilities, and compete in a competitive world of work. These works also reflect changing priorities in life, where materialistic values often conflict with the search for meaning and true happiness. The author invites the audience to reflect on the complex journey of today's young generation and provides a message about the importance of awareness of the Quarter life crisis, the role of the Sandwich generation, and the impact of Hustle culture. This conclusion illustrates that art has an important role in stimulating reflection and discussion regarding relevant social and psychological issues in contemporary society.Keywords: quarter life crisis, painting.AbstrakSalah satu peristiwa yang terjadi saat seseorang bertransisi dari masa remaja ke dewasa adalah Quarter life crisis. Quarter life crisis merupakan kondisi di mana seseorang merasa khawatir karena ketidakpastian tentang masa depan. Khawatir ini berkaitan dengan hubungan sosial, karier, dan kehidupan sosial yang dialami oleh individu di usia 20-30 tahun. Penulis akan mengundang para pembaca untuk mengkaji beberapa faktor yang menjadi penyebab Quarter life crisis dan bagaimana cara mengatasinya berdasarkan pengalaman penulis yang diungkapkan melalui seni lukis. Karya seni ini dibuat oleh seniman dengan tujuan untuk merenungkan kondisi di sekitarnya, mendorong masyarakat untuk lebih kritis terhadap lingkungannya, dan bersama-sama belajar untuk menciptakan kehidupan yang lebih baik di masa depan. Hasil dari seluruh karya lukis ini adalah penggabungan visual yang kuat dari tiga konsep utama, yaitu Quarter life crisis, Sandwich generation, dan Hustle culture. Melalui lukisan-lukisan ini, penulis berhasil menggambarkan kompleksitas tantangan yang dihadapi oleh generasi muda dalam transisi ke dewasa, dengan tekanan untuk menemukan makna hidup, memenuhi tanggung jawab keluarga, dan bersaing di dunia kerja yang kompetitif. Karya-karya ini juga mencerminkan perubahan prioritas dalam kehidupan, di mana nilai-nilai materialistik seringkali bertentangan dengan pencarian makna dan kebahagiaan sejati. Penulis mengajak audiens untuk merenungkan perjalanan kompleks generasi muda saat ini dan memberikan pesan tentang pentingnya kesadaran akan Quarter life crisis, peran generasi Sandwich, serta dampak dari budaya Hustle culture. Kesimpulan ini menggambarkan bahwa seni memiliki peran penting dalam merangsang refleksi dan diskusi mengenai isu-isu sosial dan psikologis yang relevan dalam masyarakat kontemporer.Kata Kunci: quarter life crisis, karya lukis.Author:Ummi Shabrina Damas : Institut Seni Indonesia Yogyakarta References: Ahmed, S. (2019). Hustle Culture: Examining The Socio-Cultural Drivers of Overwork Amongst Millennials. The Sociological Review, 67(2), 285“303.Arnett, J. J. (2014). Emerging Adulthood. Oxford: University Press.Asa, F. O., & Sahrul, N. (2018). Kehidupan Surau Di Minangkabau Sebagai Inspirasi Dalam Karya Seni Lukis. Gorga: Jurnal Seni Rupa, 7(2), 148-155.Ayuningtari, A. W. K. (2022). Youth Cyberbullying Sebagai Tema Penciptaan Karya Seni Lukis. Gorga: Jurnal Seni Rupa, 11(2), 521-528.Balzarie, E. N. , & N. E. (2019). Kajian Resiliensi pada Mahasiswa Bandung yang Mengalami Quarter life crisis. Prosiding Psikologi, 5(2), 494“500.Daniati, N., Sastra, A. I., & Dharsono, D. (2018). Perempuan Kerinci sebagai Ide dalam Penciptaan Karya Seni Lukis. Gorga: Jurnal Seni Rupa, 7(2), 129-133.Given, L. (2008). The SAGE Encyclopedia of Qualitative Research Methods. California: SAGE Publications, Inc.Hayslip, B. , Jr. , & F. C. A. (2018). The Sandwich generation: Challenges and Coping Strategies of Multigenerational Families. London: Routledge.Jahja, Y. (2011). Psikologi Perkembangan. Jakarta: Kencana.Newport, C. (2016). Deep Work: Rules for Focused Success in a Distracted World. New York: Grand Central Publishing.Miya, T. (2015). Do What You Love: And Other Lies About Success and Happiness. New York: Regan Arts.Poswolsky, A. S. (2016). The Quarter-Life Breakthrough: Invent Your Own Path, Find Meaningful Work, and Build a Life That Matters. New York: Tarcher Perigee.Seragih, Y. G., & Azis, A. C. K. (2021). Tinjauan Hasil Gambar Ilustrasi Kartun dengan Objek Binatang. Ekspresi Seni: Jurnal Ilmu Pengetahuan dan Karya Seni, 23(2), 302-318.Thompson, C. (2006). Art practice as research: A review essay. International Journal of Education & the Arts, 7(3), 1-13.Wibowo, A. S. (2017). Mantra kehidupan¯: Sebuah Refleksi Melewati Fresh Graduate Syndrome & Quarter-Life Crisis¯: Krisis Seperempat Baya. Jakarta: PT. Elex Media Komputindo.